PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL UNTUK MENINGKATKAN KEMAMPUAN MENDESKRIPSIKAN KERAGAMAN BUDAYA KELAS IV DI SEKOLAH DASAR NEGERI KAYUNAN - Ayu Fari Hatul Jannah; Alfi Laila; Muhammad Basori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is driven by the low ability of students to describe cultural diversity, caused by the inappropriate use of teaching media. The aim of this study is to enhance the validity of the development of interactive android-based learning media in Social Studies for fourth-grade elementary school students, to determine the practicality of this media on the topic of Cultural Diversity, and to measure its effectiveness. The research model used is Research and Development (R&D) with the ADDIE development model design. The study was conducted at Kayunan State Elementary School with 46 fourth-grade students as subjects. Data collection techniques include documentation, observation, and questionnaires. Data collection instruments include interviews, validation sheets, and student response questionnaires. The research results show that the interactive android-based learning media is very valid with a validity score of 95% from media and material experts, very effective with a percentage of 91%, and very practical with a score of 92.35%. The researcher concludes that this media can improve students' descriptive abilities and help make learning more student-centered. It is recommended that Kayunan State Elementary School continue to develop this interactive learning media.